Reflective journals: enhancing doctoral students' engagement. Issue 3 (4th May 2021) - Draissi, Zineb; BaoHui, Zhang; ZhanYong, Qi
ABSTRACT: Reflection journals (RJs) have been recognised as a vital tool in promoting student learning. However, little is known about how doctoral students use RJs to improve academic engagement. Through a mixed-method study, this paper explored how six international students from a Chinese normal university utilized RJs in their engagement in an advanced learning sciences course. This study used reflective journals, surveys, and interviews to examine doctoral students' perceptions of the effectiveness of reflective journals in their learning process in a 12-week 'Frontiers of the Learning Sciences' course. The quantitative results revealed that all items received a positive rating and were appropriate for exploring how reflective journals enhanced the participants' critical thinking, writing skills and engagement. Overall, the findings confirmed that reflective journals facilitate critical thinking, metacognition, and self-engagement. The findings of the study likewise provide information for course instructors to adjust their lesson plans in response to students' comments and suggestions.